Novel platelet-agglutinating protein from a thrombotic thrombocytopenic purpura plasma. - Siddiqui, F A (1985)
A novel platelet-agglutinating protein (PAP) was purified approximately 2,000-fold from the plasma of a patient with thrombotic thrombocytopenic purpura (TTP) by ammonium sulfate fractionation, DEAE-Sephacel and concanavalin A-Sepharose chromatographies. On sodium dodecyl sulfate-polyacrylamide gel electrophoresis, with and without reduction, this preparation revealed a major protein band with a molecular weight of 37,000, and a minor band with a molecular weight of 32,000-34,000. After elution from the gel, only the 37,000-mol wt protein corresponding to the major band induced the platelet agglutination. When four normal plasmas and the recovery plasma from the same TTP patient were subjected to the similar purification steps, the 37,000-mol wt major band was absent. The 125I-PAP bound to the platelets in a concentration-dependent manner. The platelet agglutination induced by PAP was not inhibited by hirudin, heparin in the presence of antithrombin III, phenylmethylsulfonyl fluoride, apyrase, aspirin, or prostaglandin I2. However, it was inhibited by IgG from normal adults and from the same TTP patient after recovery. The anti-37,000-mol wt PAP antiserum prepared in the rabbit formed a single precipitin line against the highly purified PAP. Using this antiserum in the Western immunoblotting, the 37,000-mol wt protein band was found in the three TTP plasmas, of which the platelet-agglutinating activity was inhibited by the anti-37,000-mol wt PAP IgG. The 37,000-mol wt immunoprecipitin band was absent in the plasmas obtained from another two TTP patients, two normal subjects, two patients with idiopathic thrombocytopenic purpura, and two patients with disseminated intravascular coagulation. These results suggest that the 37,000-mol wt PAP is present only in certain cases of TTP, and is likely to be responsible for the formation of platelet thrombi in the microcirculation.